NILAI PENDIDIKAN KARAKTER DALAM CERITA ANAK PADA RUBRIK ANAK HARIAN KOMPAS MINGGU - Normawati NFN (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Children literary always be the wet part to work. The children short story is a instrument of learning in characters building. So that, this research goals to express about the character values on Kompas short stories that was published on April 2014 until April 2015. The data was collected by reading technique and understand to children short stories. Data was analyzed by descriptive qualitative. Its result was shown about religious, honesty, discipline, responsibility, care, friendly, patriotism, positive thinking, to respect, creative, economical, and hard work value. More add, commonly its structure is appropriate to spirit growing of SD students and themselves.